Semasiologis Dalam Bahasa Toraja - Resnita Dewi; Paulina Pulung; Abdul Muttalib (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2018)
This study aims to describe semasiologi in Toraja. This research is a type of comparative qualitative research. The data in this study were Toraja based on two hundred Gloss Swadesh collected from informants in five research locations, namely Rembon, Makale, Salubarani, Sa'dan, and Baruppu. Data was collected using interview techniques and noted. The results of the study show that semasiologically found in Toraja. Semasiologi refers to the meaning of two forms of the same language but has different concepts or meanings. Semasiology in the Toraja language can be found in the words sia, sola, tambuk, penaa, ula ', baine, muane, and five.